Stabilization of chromatin structure by PRC1, a Polycomb complex. - Shao, Z.; Raible, F.; Mollaaghababa, R.; Guyon, J.R.; Wu, C.T.; Bender, W.; Kingston, R.E. (Cell, 1999)
The Polycomb group (PcG) genes are required for maintenance of homeotic gene repression during development. Mutations in these genes can be suppressed by mutations in genes of the SWI/SNF family. We have purified a complex, termed PRC1 (Polycomb repressive complex 1), that contains the products of the PcG genes Polycomb, Posterior sex combs, polyhomeotic, Sex combs on midleg, and several other proteins. Preincubation of PRC1 with nucleosomal arrays blocked the ability of these arrays to be remodeled by SWI/SNF. Addition of PRC1 to arrays at the same time as SWI/SNF did not block remodeling. Thus, PRC1 and SWI/SNF might compete with each other for the nucleosomal template. Several different types of repressive complexes, including deacetylases, interact with histone tails. In contrast, PRC1 was active on nucleosomal arrays formed with tailless histones.